2009
DOI: 10.1002/app.29585
|View full text |Cite
|
Sign up to set email alerts
|

Polypropylene/clay nanocomposites: Effect of different clays and compatibilizers on their morphology

Abstract: A set of organically modified clays (OLS) were mixed with different compatibilizers to alter their interactions with either homopolymer or heterophasic polypropylenes when they were melt-mixed, and the relation between the OLS/compatibilizer system and the composite morphology was studied. X-ray diffraction (XRD) showed that depending on the specific OLS/compatibilizer system, it is possible to obtain several morphologies in the composites. In particular, some samples prepared with compatibilizers based on ita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 37 publications
2
34
0
1
Order By: Relevance
“…Maleic anhydridegrafted thermoplastic polymers are the most common coupling agent used in WPC (Kim et al 2007, Cui et al 2008, Poletto et al 2014. However, other polar monomers from sustainable resources such as itaconic acid and its derivatives have been studied recently (Toro et al 2007, Palza et al 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maleic anhydridegrafted thermoplastic polymers are the most common coupling agent used in WPC (Kim et al 2007, Cui et al 2008, Poletto et al 2014. However, other polar monomers from sustainable resources such as itaconic acid and its derivatives have been studied recently (Toro et al 2007, Palza et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…It is a white crystalline unsaturated dicarbonic acid with one carboxyl group conjugated to the methylene group (Willke and Vorlop 2001). Due to its double functionality, itaconic acid and its derivatives offer interesting possibilities as polar functional monomers for the modification of polyolefins and used as coupling agent in composite formulations (Toro et al 2007, Palza et al 2009). The utilization of itaconic acid as polar monomer grafted in polyolefins can be considered important because of its carboxylic bifunctionality and also due to the fact that itaconic acid is produced from non-oil based renewable natural resource, i.e., by large scale fermentation of molasses, a by-product from sugar industry (Bruna et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, different PPs, organic clays, and compatibilizers were used in this work to prepare composites with several morphologies. In a previous contribution, [29] it was shown that these composites present several hierarchical structures, from tactoid to intercalated and well-dispersed clays, depending on the specific PP/clay/ compatibilizer system used. In the present contribution, the thermal stability of these composites were analyzed by means of thermogravimetric analysis (TGA) under either inert or thermo-oxidative conditions and the effect of the composite hierarchical structure is discussed in detail.…”
Section: Introductionmentioning
confidence: 99%
“…It may happen because of structural dehydration or the collapse of the structure in final polymer composite. A less intense and wider reflex (001) implies an intercalated-exfoliated structure [15]. 2θ/°I ntensity/a.u.…”
Section: Xrdmentioning
confidence: 99%